Enough! : 20 protesters who changed America - Easton, Emily (Crown Books for Young Readers, 2018)
"From Samuel Adams to the students from Parkland, march through history with the heroic revolutionary protesters who changed America. These heroic protesters were not afraid to stand up for what they believed in. They are among the twenty change-makers in this book who used peaceful protests and brave actions to rewrite American history"--Jacket.